2013
DOI: 10.1371/journal.pone.0060561
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lactate/ATP Ratio, as an Alarm Index and Real-Time Biomarker in Critical Illness

Abstract: ObjectiveThe acute physiology, age and chronic health evaluation (APACHE) II score and other related scores have been used for evaluation of illness severity in the intensive care unit (ICU), but there is still a need for real-time and sensitive prognostic biomarkers. Recently, alarmins from damaged tissues have been reported as alarm-signaling molecules. Although ATP is a member of the alarmins and its depletion in tissues closely correlates with multiple-organ failure, blood ATP level has not been evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, we found the opposite as ATP efflux decreased in hypoxic septic RBCs. Consistent with this inhibition of RBC ATP efflux and decreased plasma ATP levels in septic rats is the finding that plasma ATP levels are decreased in critically ill patients [ 35 ].…”
Section: Discussionmentioning
confidence: 75%
“…However, we found the opposite as ATP efflux decreased in hypoxic septic RBCs. Consistent with this inhibition of RBC ATP efflux and decreased plasma ATP levels in septic rats is the finding that plasma ATP levels are decreased in critically ill patients [ 35 ].…”
Section: Discussionmentioning
confidence: 75%
“…We found that mitochondrial activity in lymphocytes of septic patients is impaired, which may be an underlying cause of T cell suppression in these patients. This notion is supported by findings that oxygen consumption of peripheral blood mononuclear cells is lower in sepsis patients than in patients without sepsis (48,49) and that the cellular ATP content of circulating cells is lower and lactate levels are higher in sepsis patients compared with patients without sepsis (50).…”
Section: Discussionmentioning
confidence: 78%
“…Blood cells become diluted by transfusion, and a low red blood cell (RBC) count is usually found in patients with advanced disease, resulting in a low blood level of ATP in those who are severely ill (11). Since the major source of ATP in blood is RBCs, the blood ATP levels in the present study were normalized by the level of tHgb (ATP/tHgb).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, blood ATP depletion has been identified in children with influenza-associated acute encephalopathy (9). Although released ATP cannot be accurately analyzed due to rapid degradation, the cellular ATP level, including the blood cell ATP level, is easily measured with a bedside procedure that uses the sum of ATP production and ATP degradation and/or release (10, 11).…”
Section: Introductionmentioning
confidence: 99%